Perilaku Konsumtif Penggemar AKB48: Studi Kasus Mahasiswa Bahasa dan Sastra Jepang Universitas Airlangga - Nur Kumala Hapsari, Meilani; Syafik, Abdurrahman; Isya Putra, Maulana; Ikbal, Maulana; Rachmasari, Firtha Ayu (Japanology: The Journal of Japanese Studies, 2024)
It can be said that there are quite a lot of Japanese idol fans in Indonesia, especially among young adults aged 18-29 years. This research analyzes the consumer behavior of fans of the idol group AKB48 using a case study of Japanese Language and Literature students at Airlangga University. Japanese Language and Literature students are relevant to research because their average age is 18-29 years. The researcher assumes that Japanese Language and Literature students can represent a group of young adults who have an interest in Japanese popular culture. This research is qualitative research with a case study approach. Determining the informants themselves used snowball sampling and four informants were obtained. Data collection techniques in this research used in-depth interview. The data found was analyzed through Jean Baudrillard's theory of consumerism. The results of the research show that there is consumptive behavior carried out by the four Japanese Language and Literature students who are fans of AKB48. Visible consumer behavior includes buying products promoted by AKB48 members, collecting goods and knick-knacks from AKB48, collecting DVDs/CDs, watching online and offline concerts, attending fan meetings, and holding birthday celebrations for AKB48 members and others.